Examining the violentisation process and the likelihood of first time offenders becoming dangerous violent perpetrators, amongst offenders diverted from various courts in the Western Cape - Ross, Ashleigh (Department of Social Development, 2020)
The purpose of this quantitative cross-sectional study was to test the Violentization process with a group of first time adult male offenders charged with Assault Common or Assault GBH diverted from various courts in the Western Cape. The results of the study were compared to that of a similar study conducted by Holtzhausen (2015) which was done on a group of male youths from two townships in the Western Cape. With regards to this study individual interviews were conducted with 50 adult male participants between the ages of 18 and 65 respectively who were charged with one of the above offences and who were found suitable for diversion. The findings revealed that there were slight differences which could be due to the fact that the results of the study done by Holtzhausen (2015) were done with individuals who had been in conflict with the law on more than one occasions and some participants had also been incarcerated, compared to the participants of this study who were first time offenders. Furthermore, the results indicated that the majority of participants showed medium exposure and thus shows that they have in fact completed at least one or more but not all of the stages of Athens (1989) theory of Violentization. Based on the findings of this study, it is recommended that this research and its research process and data collection tool be relooked in terms of its applicability to the South African context and further be used as an assessment tool and measurement instrument in intervention services provided to persons by social workers and probation officers in various settings, such as correctional centres, courts and NGO’s.